Analysis of factors influencing housewives to choose PNM Mekaar and BTPN Syariah financing - Nuraini, Nuraini; Syahriza, Rahmi; Yanti, Nursantri (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
Financial institutions in the community are growing rapidly, especially with financing options from PNM Mekaar and BTPN Syariah. This study aims to determine the factors that affect the choice of homemakers for financing from PNM Mekaar and BTPN Syariah. This study uses a quantitative methodology using primary data obtained from the distribution of questionnaires, interviews, and observations. The study was conducted in two hamlets with a sample of 67 people using a saturated sampling strategy that covers the entire population. The results of the research and discussion show that economic variables and financing needs significantly affect the choice of homemakers for financing from Mekaar and BTPN Syariah in Tasak Baru and Tasak Lama Hamlets. The aspect of financial knowledge does not affect financing decisions. Meanwhile, economic factors, financial knowledge, and financing requirements simultaneously affect the choice of financing options. Public interest statements This result provides information and understanding regarding the factors influencing homemakers' financing choices between PNM Mekaar and BTPN Syariah.